Integrin α2 is an early marker for osteoclast differentiation that contributes to key steps in osteoclastogenesis - Brockhaus, Katrin; Hemsen, Isabel; Jauch-Speer, Saskia-Larissa; Niland, Stephan; Vogl, Thomas; Eble, Johannes A. (Frontiers in Cell and Developmental Biology, 2024)
Osteoclasts (OCs) determine bone tissue turnover. Their increased activity causes osteoporosis, their dysfunction osteopetrosis. Murine monocytic ER-Hoxb8 cells differentiate into OCs upon treatment with M-CSF and RANKL and upregulate the collagen-binding integrin α2β1 distinctly earlier than other OC markers, such as the OC-associated receptor, OSCAR. Integrin α2β1 promotes OC differentiation at multiple levels by stimulating differentiation-relevant genes, by regulating cell matrix adhesion and the formation of adhesion-promoting protrusions, and by the upregulation of proteins involved in precursor cell fusion. The two key factors in osteoclastogenesis, RANK and NFATc1, were essentially unaffected after knocking out the ITGA2 gene encoding integrin α2 subunit. However, compared to integrin α2β1 expressing ER-Hoxb8 cells, ITGA2-deficient cells adhered differently with more branched filopodia and significantly longer tunneling nanotubes (TNTs). Despite the higher number of fusion-relevant TNTs, they form fewer syncytia. They also resorb less hydroxyapatite, because integrin α2β1 regulates expression of lacuna proteins necessary for bone matrix resorption. The impaired syncytia formation of ITGA2-deficient OC precursor cells also correlated with reduced gene activation of fusion-supporting DC-STAMP and with an almost abolished transcription of tetraspanin CD9. CD9 only partially colocalized with integrin α2β1 in TNTs and filopodia of integrin α2β1-expressing OC precursors. Our findings define integrin α2β1 as an early marker of OC differentiation.